SYMBIOTIC POSTHUMANIST ECOLOGIES IN WESTERN LITERATURE, PHILOSOPHY AND ART - WENYI PANG (Journal of Dharma, 2024)
This book builds on the previous works and shifts away from ecohumanism and anthropocentrism to critical theory. The editors affirm that posthumanism serves as a valuable lens for navigating contemporary conditions, emphasizing dignity for all beings. The contributing authors engage deeply with the concept of symbiosis, offering insights into what it means to exist as posthuman humans in both theory and practice in the 21st century. Through interdisciplinary dialogues—particularly across Western literature, philosophy, and art—the book revisits themes in mythology, engineering, and aesthetics. It explores human-more-than-human relations, advocates symbiocentric politics, and reflects on the future of both the Humanities and humanity.